Perbaikan Sistem Hukum Dalam Pembangunan Hukum Di Indonesia - Azmi Fendri (Fakultas Hukum Universitas Riau, 2010)
Since reform marked by fall downing regime himGovernance of New Order, peeping out a period totransition in course of democracy. Word democratizelikely become tidy political jargon in the form of socialissues and HAM which later then diekspos to societyto oppose all policy of governance. Proper confessedduring governance of New Order, democracy likelybecome very matter of taboo to be talked openlypublic. This matter of mirror from various legislationproduct which do not express justice of society ingeneral.